Against Editing: The algorithm as a narrative process - Margaritis, Charalambos (My University, 2024)
This presentation concerns an ongoing art-based research on the ways to apply principles of dynamic and multicursal narrative design of video games - such as open-world game design, quest systems, branching narrative structures and multiple endings - on animated storytelling. The research aims at proposing a model of animated storytelling which makes full use of available digital tools and ludological theory instead of digitally mimicking analogue processes. In this framework, the central process of analogue animated storytelling, editing, is critically assessed under the light of Lev Manovich’s theory on digital cinema and database aesthetics. The 20th century can be understood as a transitional period where the notion of the database becomes more and more prominent, simply because cataloguing (the preexisting relevant cultural process) obtains the property of the recorded catalogue. This possibility to index the actual direct traces and imprints of reality progressively places the concept of the catalogue in the centre of the cultural paradigm of western society. A film can be seen as the result of the selection of a group of shots among a catalogue of takes - subsequently, editing, can be seen as the process of selection and ordering. In the microscopic level of the animated film, the equivalent is valid for the individual frames. A database is the digital form of the catalogue, an augmented version of the catalogue - a catalogue that can be dynamic, reconfigurable, ever-changing and more aptly interfaced inviting (and allowing) endless permutations and combinations of its items. The paradigm is no longer that of the catalogue who is edited to create versions of itself or comprehensive lists of selections of its items; the paradigm is that of the database in which we iterate through the use of the algorithm. Through an animated short film that will be presented and broken down, this presentation demonstrates a practical application of this novel idea and set of capabilities it renders possible for animated film. The film is created following the logic of the database and puts to use principles of dynamic reconfiguration - such as multicursivity, recursion, looping and repetition. The function served by editing (as a set of choices taken at a specific point in time prior to the screening of the film) is now fulfilled by a process of dynamic (live) movement.
Keywords: animation; film editing; narrative; storytelling